E-Learning Training Activities for Lecturers - Dabella Yunia (MOVE: Journal of Community Service and Engagement, 2021)
This E-Learning workshop aims to improve lecturers' mastery in utilizing one of the E-Learning platforms, namely Edmodo. This is done as a means for lecturers to carry out teaching and learning activities without being limited by time and place. From the whole series of activities in this training program, several conclusions can be drawn that Edmodo can be used as an alternative to E-Learning learning media that is easy to use and apply to the campus environment.